Unifying Types of Access Permissions to Information Resources of Cloud Web-services - Pavel Petrovich Keyno (Безопасность информационных технологий, 2015)
The article describes the technique of generalization of access permissions to different parts of Web-pages The permissions of each part divides into create, read, update and delete ones for each user or group. It is based on the principles of organizing permissions in UNIX-like operating systems and CRUD.